Training Technologies as a Means of Communicative Competences Development of Prejudicial Inquiry Agencies’ Investigators - Miloradovа, N. E.; Мілорадова, Н. Е.; Okhrimenko, I. M.; Орхіменко, І. М.; Dotsenko, V. V.; Доценко, В. В.; Matiienko, T.; Rivchachenko, O.; Natalia Miloradova; Вікторія Доценко (Postmodern Openings. – 2022. – Vol. 13, Issue 2. – P. 01-22, 2022)
Комунікативний компонент професійної діяльності слідчого є домінуючим, оскільки свідчить про здатність працівника організовувати роботу на основі професійно виваженого спілкування з об’єктами взаємодії. Етап здобуття вищої освіти у закладах зі специфічним навчальним середовищем є сензитивним періодом для розвитку основних соціогенних структур особистості та становлення професійної ідентичності майбутніх фахівців.

The communicative component of the investigator’s professional activities is a dominant one, as it demonstrates the employee’s ability to organize work on the basis of professionally balanced communication with the objects of interaction. The stage of obtaining higher education in institutions with specific learning environment is a sensitive period for the development of the main sociogenic structures of personality and the development of professional identity of future professionals. This period is characterised by a purposeful mastering o f the system of professional knowledge and skills, formation of a holistic view of the professional community, which results in awareness of professional readiness. The use of training technology in the training of investigators helps to increase the efficiency of the professional training process, based on the basic principles of personality - oriented education. The aim of our research is to study the process of formation of components of communicative competence in future investigators of prejudicial inqui ry agencies with the help of training technologies. Appropriate psychodiagnostic tools were used to solve this purpose, which was tested during the training of specialists for prejudicial inquiry agencies. Most of the respondents stated the existence of satisfaction with participating in the training courses, awareness of the importance of its informativeness and practical orientation. Post-training testing emphasized the participants’ rethinking of the value of interpersonal relations; growing desire to help and show warmth and friendliness in relations with others; the expediency and effectiveness of the use of cooperation and compromise in resolving conflict situations within a professional and personal environment.

Коммуникативная составляющая профессиональной деятельности следователя является доминирующей, так как демонстрирует способность работника организовать работу на основе профессионально сбалансированного общения с объектами взаимодействия. Этап получения высшего образования в учреждениях со специфической учебной средой является сенситивным периодом для развития основных социогенных структур личности и формирования профессиональной идентичности будущих специалистов.
Keywords: Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; training technologies; communicative competence; interpersonal relations; investigators; professional training; professional training of investigators; технології навчання; комунікативна компетентність; міжособистісні стосунки; професійна підготовка; слідчі; вищі навчальні заклади зі специфічними умовами навчання; высшие учебные заведения со специфическими условиями обучения; higher education institution with specific conditions of learning; технологии обучения; коммуникативная компетентность; межличностные отношения; следователи; профессиональная подготовка